Chinese Investment and Icelandic National Security - Sveinn K. Einarsson 1982-; Bailes, Alyson J.K., 1949-; Ingjaldur Hannibalsson 1951- (2014)
A debate has been on-going in the western world regarding the costs and benefits of foreign direct investment originating in China. While some policy- makers and members of the public welcome the much-needed infusion of finance and the employment it creates, others perceive it as not only being made with commercial interests in mind, but rather as part of a larger strategy by China aimed at gaining a strategic foothold in the region. The article examines whether the trend of increased foreign direct investment by Chinese business entities in Iceland poses a threat to the national security of the receiving country. Economic factors as well as official policy will are identified as the key drivers behind the recent surge in Chinese outward foreign direct investment. Icelandic public and official reactions to the phenomenon will be discussed and Barry Buzan ́s definition of security will be applied in order to determine whether and what kind of threats Chinese foreign direct investment poses to the national security of Iceland. The article concludes that the phenomenon of foreign direct investment originating in China does not pose an imminent threat to the military security of Iceland nor its allies. On the contrary, it seems that the strategic threat posed by increased Chinese investments within Iceland is overstated by the media. Chinese foreign direct investment could certainly pose challenges to some aspects of Icelandic security but these do not include hard national security threats.